Importance of patient bed pathways and length of stay differences in predicting COVID-19 hospital bed occupancy in England - Leclerc, QJ; Fuller, NM; Keogh, RH; Diaz-Ordaz, K; Sekula, R; Semple, MG; Atkins, KE; Procter, SR; Knight, GM; Horby, P (BioMed Central, 2021)
Background: Predicting bed occupancy for hospitalised patients with COVID-19 requires understanding of length of stay (LoS) in particular bed types. LoS can vary depending on the patient’s “bed pathway” - the sequence of transfers of individual patients between bed types during a hospital stay. In this study, we characterise these pathways, and their impact on predicted hospital bed occupancy.